1999
DOI: 10.1037/0882-7974.14.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture and aging: Implications for visual search performance and oculomotor control.

Abstract: Two studies examined potential age-related differences in attentional capture. Subjects were instructed to move their eyes as quickly as possible to a color singleton target and to identify a small letter located inside it. On half the trials, a new stimulus (i.e., a sudden onset) appeared simultaneously with the presentation of the color singleton target. The onset was always a task-irrelevant distractor. Response times were lengthened, for both young and old adults, whenever an onset distractor appeared, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 91 publications
12
66
0
Order By: Relevance
“…We did not Wnd this pattern in our paradigm, as there was no decrease in the accuracy of the inhibitory motor control with aging, although there was a general slowing and increased variability in both online and inhibitory movements to both perturbed and unperturbed targets. Our data does agree with previous Wndings on oculomotor inhibition where aging did not result in increased capture eVects (Eenshuistra et al 2004;Colcombe et al 2003;Kramer et al 1999). Interestingly, Kramer et al (2000) found that both elderly and young participants misdirected their saccades in an equivalent proportion of trials when awareness of the distracter was low, but when the distracter was brighter than the search stimuli older subjects were less eYcient in inhibiting saccades towards these distracters.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We did not Wnd this pattern in our paradigm, as there was no decrease in the accuracy of the inhibitory motor control with aging, although there was a general slowing and increased variability in both online and inhibitory movements to both perturbed and unperturbed targets. Our data does agree with previous Wndings on oculomotor inhibition where aging did not result in increased capture eVects (Eenshuistra et al 2004;Colcombe et al 2003;Kramer et al 1999). Interestingly, Kramer et al (2000) found that both elderly and young participants misdirected their saccades in an equivalent proportion of trials when awareness of the distracter was low, but when the distracter was brighter than the search stimuli older subjects were less eYcient in inhibiting saccades towards these distracters.…”
Section: Discussionsupporting
confidence: 78%
“…Based on the studies reviewed here we would expect elderly subjects to be delayed in the onset of their online correction to a target perturbation (see Sarlegna 2006), but possibly be accurate in carrying out such a correction. Regarding the movement inhibition in the stop condition, we would expect impairment with age, yet the oculomotor capture results by Kramer et al (1999; would not support such an assumption.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The proportion of saccades towards the distractor and the difference in search time for valid and invalid trials are used as measures of oculomotor capture. Although several studies have found general age-related deficits in inhibition (de Fockert, Ramchurn, van Velzen, Bergstroem, & Bunce, 2009;Hasher & Zacks, 1988), Kramer et al (1999) found that young and older adults made equal number of saccades towards the distractor thus suggesting that oculomotor control was age irrelevant. However, subsequent studies have shown an age-related effect if the distractor was extra salient (Kramer, Hahn, Irwin, & Theeuwes, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that humans and other organisms have an automatic response tendency to direct both their attention (see for a review, Yantis, 1998) and their eyes (Roberts et al, 1994;Theeuwes, Kramer, Hahn, & Irwin, 1998) toward abrupt visual onsets. Kramer et al (1999) examined the effect of abrupt onset distractors on goal-directed eye movements in a visual search task. Younger and older adults misdirected their eyes to the distractor onset on an equally large portion of the trials before moving their eyes to the target.…”
mentioning
confidence: 99%